La expresión plástica y su influencia en el desarrollo de la motricidad fina de los niños y niñas del nivel 2 del centro educativo “Corazón De Jesús” del cantón Chambo, provincia de Chimborazo. periodo lectivo 2013-2014”. lineamientos alternativos - González Bautista, Andrea Marisol (2015)
his thesis refers to "PLASTIC EXPRESSION AND ITS INFLUENCE ON THE DEVELOPMENT OF FINE MOTOR SKILLS OF CHILDREN'S EDUCATIONAL CENTER LEVEL 2" Heart of Jesus "CANTON Chambo, Chimborazo province. School period 2013-2014 ". Alternative guidelines, made according to the provisions of Regulation Academic Board of the National University of Loja. He was raised as General Objective: To know the importance of Plastic Expression in the Development of fine motor children Education Center Level 2 "Heart of Jesus" Canton Chambo, Chimborazo province. 2013-2014 school. Alternative guidelines. The central problem of the research was: How Plastic Expression influences in the development of fine motor skills of children level 2 School "Heart of Jesus" Canton Chambo, Chimborazo province. 2013-2014 school. Alternative guidelines? The methods used for the preparation of this research work were: Scientific, inductive-deductive, analytic-synthetic, Descriptive and Statistical Model. The techniques and instruments used were: a survey of teachers of children of school Level 2 "Heart of Jesus", to set the use of the plastic expression of children and an Observation applied to children school level 2 "Heart of Jesus" to evaluate Fine Motor children. It is concluded that: 100% of the surveyed teachers active in the daily work with children using tearing, bucking, color and skewered. Teachers use elements of artistic expression as textures and color to develop in children better fine motor skills as part of teaching and learning. It is observed according to the percentages obtained that teachers entrench his teachings in the curriculum model intended for basic general education since the implementation of each of the leaders the objectives are achieved within the kindergarten. Regarding Observation Guide applied to children of school Level 2 "Heart of Jesus", to assess fine motor children, the results determine that: 58% of girls and boys perform all observed and each of the proposed activities, showing his fine motor skills with the application of techniques such as Trozado, Skewered, Color, Torn, and the technique of cotton balls, earning a rating of Highly Satisfactory, Satisfactory 35%; and 7% Unsatisfactory. It is concluded that teachers in the development of fine motor skills of children have the clear intention in carrying out the different techniques and that all jobs have a significance